Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/biot.201700766
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐Down Model Development in ambr systems: An Industrial Perspective

Abstract: High‐Throughput (HT) technologies such as miniature bioreactors (MBRs) are increasingly employed within the biopharmaceutical manufacturing industry. Traditionally, these technologies have been utilized for discrete screening approaches during pre‐clinical development (e.g., cell line selection and process optimization). However, increasing interest is focused towards their use during late clinical phase process characterization studies as a scale‐down model (SDM) of the cGMP manufacturing process. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…For the purposes of fermentation process development, bench scale bioreactors allow for accurate measurement and control of pH, dissolved oxygen, temperature, as well as the automated addition of nutrients and chemical inducers during cell growth. In recent years, automated parallel bioreactor systems have accelerated fermentation process development by combining smaller volumes and higher throughput to enable greater iteration than traditional benchtop bioreactors [84][85][86] .…”
Section: Manufacturability Of Engineered Live Bacterial Therapeuticsmentioning
confidence: 99%
“…For the purposes of fermentation process development, bench scale bioreactors allow for accurate measurement and control of pH, dissolved oxygen, temperature, as well as the automated addition of nutrients and chemical inducers during cell growth. In recent years, automated parallel bioreactor systems have accelerated fermentation process development by combining smaller volumes and higher throughput to enable greater iteration than traditional benchtop bioreactors [84][85][86] .…”
Section: Manufacturability Of Engineered Live Bacterial Therapeuticsmentioning
confidence: 99%
“…A mini-chemostat (MC) system (16 reactors with 40 ml working volume) was developed to characterize yeast physiology, and it was shown that the MC system provided the same environmental conditions as the DASGIP R parallel bioreactor system (Eppendorf) (Bergenholm et al, 2019). In a recent review, a systematic approach toward scale-down model (SDM) development in ambr 15 systems was described, and it was suggested that ambr SDMs are suitable for future regulatory submissions (Sandner et al, 2018). In a study by Vit et al (2019), the efficiency of a microfluidic cell cultivation device and its applicability for rapid screening of multiple parameters was also established.…”
Section: High-throughput Cultivation Systemsmentioning
confidence: 99%
“…Parallel miniature bioreactors with small working volumes (also called microbioreactor systems) are an important alternative to the traditional batch cultivation apparatuses for use in bioprocess development and scale-up/scale-down investigation. Many important studies offer a detailed discussion of this topic, and many commercialized products (e.g., DASGIP from Eppendorf, AMBR from Sartorius Stedim Biotech) are also available in the market (Faust et al, 2014;Hemmerich et al, 2018a;Bjork and Joensson, 2019;Sandner et al, 2019;Znidarsic-Plazl, 2019). Process monitoring and control of miniature bioreactors are more complicated than single-bioreactor control, but investigations have shown encouraging results.…”
Section: Expanding the Application Of Cutting-edge Bioreactor Controlmentioning
confidence: 99%